The Disappearing IPO Puzzle and the Shift Toward Acquisitions: New Insights from Proprietary U.S. Census Data on Private Firms - Chemmanur, Thomas; He, Jie (Jack); Ren, Xiao (Shaun); Shu, Tao (The Review of Corporate Finance Studies, 2025)
Abstract The IPO volume in the US significantly decreased after 2000, as more entrepreneurial firms exited through acquisitions rather than IPOs. Using proprietary U.S. Census data on private firms, we examine several new hypotheses to explain these phenomena. Our results support explanations based on standalone public firms’ greater sensitivity to product market competition as well as private firms’ obtaining access to more abundant PE financing in the post2000 era. In contrast, we do not find evidence consistent with an eroded private firm base after 2000 or with the economies of scope explanation that mainly focuses on firm size. (JEL G32, G34, G24)